The Reality of Supplies Services provided to Cattle breeders in the Central and Southern governorates of Iraq - العبودي محمد طالب هادي; البدري اشواق عبد الرزاق ناجي (Journal of Kerbala for Agricultural Sciences, 2015)
The research aimed to identify the reality of Supplies services provided to cattle breeders in the central and southern provinces of Iraq , The research community covered ( 13 ) provinces of the central and southern area of Iraq . ( 50% ) of those provinces ( 7 provinces ) were chosen as a sample ( Baghdad , Karbala , Najaf , Wasit , Qudisya , Muthana and Basrah ) . The sample also included ( 42 ) of livestock directors , which represented ( 100% ) of the community Within of agricultural departments , to achieve the research objective a questionnaire was designed to collect data , to measure reality of Supplies services provided to Cattle breeders Consisting of five axis (Targeted group , services themes , processed quantity , government support , Presentation style) . The items consisting these axis were (19) items ; Results showed a noticeable weak and luck of Supplies services for cows breeders , as noted ( 100% ) of the units of livestock directors to that Supplies services provided do not meet the breeders needs of ration as well as other Materialism requirements , The research recommend of the necessity to introduce specialized programs in providing ration as well as other material requirements which enable the breeders to manage their cows by directors of supplies services .